Development of electronic student worksheets based on toulmin argumentation patterns to improve argumentation skills in basic acid materials - Esa Witri; Ngatijo Ngatijo; Muhammad Haris Effendi-Hasibuan (Jurnal Pendidikan Kimia (JPKim), 2020)
This research is part of a research project to help improve students' argumentative skills in chemistry subjects. This research is part of the development of argumentation-based teaching materials while other studies have developed learning models, teaching materials and a collection of argumentation questions. The purpose of this research was to determine the process of developing students' e-worksheets, the feasibility of students' e-worksheets based on concept and practitioner perceptions, and the effectiveness of students' e-worksheets that were developed as teaching materials based on the Toulmin argumentation pattern. Product trials were conducted at state senior high schools 11 Jambi City. The results of the practitioner's eligibility based on the teacher's response are in the very good category and students from both groups have a correlation in the "high" category. The effectiveness test is seen from the average N-Gain score of the experimental class in the quite effective category. There is a significant difference between the experimental class and the control class which can be seen from the difference in learning outcomes of the experimental class (using students' e-LKS based on the Toulmin argumentation pattern) higher than the control class (not using e-LKS).Keywords: Acid-base, E-student worksheet, Toulmin's argumentation pattern